Marine biologist - Wendt, Jennifer frey50 (Mankato, Minn. : Capstone Books, 2000)
Introduces the career of marine biologist, discussing educational requirements, duties, workplace, salary, employment outlook, and possible future positions.
Includes bibliographical references and index.
Keywords: Marine biologists; Marine biologists; Vocational guidance